(untitled) - Searle, John R (Cambridge, 1970)
Includes bibliographical references.; Methods and scope -- Expressions, meaning and speech acts -- The structure of illocutionary acts -- Reference as a speech act -- Predication -- Three fallacies in contemporary philosophy -- Deriving "ought" from "is."
Keywords: Speech acts (Linguistics); Semantics (Philosophy); Language and languages -- Philosophy; Nghệ thuật diễn thuyết (Ngôn ngữ học); Ngữ nghĩa học (Triết học); Ngôn ngữ học và triết học -- Triết học